IMPLEMENTASI SISTEM INFORMASI ADMINISTRASI KEPENDUDUKAN DALAM PELAYANAN KARTU TANDA PENDUDUK PADA DINAS KEPENDUDUKAN DAN CATATAN SIPIL KOTA KENDARI - La Tarifu (Journal Publicuho, 2020)
The purpose of this study is to describe the Implementation of Population Administration Information System in the Management of Identity Card Services (KTP) at the Population and Civil Registry Office of Kendari City. Data collection is done by in-depth interview techniques, observations, and document studies, while data analysis techniques are done qualitatively and quantitatively. The informant selection technique uses one of the techniques in sampling or determining the informant with consideration or certain criteria (purposive) in the Research Methodology. The results of the study indicate the factors that influence the implementation of policies that contain communication, resources and dispositions run effectively. This can be seen from good communication, technological guidance for resources and a loyal attitude towards a policy. In a no-no situation, the population administration information system is good enough. However, in the context of population registration, it has not run optimally due to inadequate facilities. While in the context of civil registration can also be seen from the work of employees always based on existing rules. Then in the context of information management, it must also be good enough to improve information and also must provide more adequate facilities.